Interest In and Practices Related to Gynecologic Oncology among Members of the Brazilian Federation of Associations of Gynecology and Obstetrics - Júnior, Arilto Eleutério da Silva; Carvalho, Jesus Paula; Derchain, Sophie Françoise Mauricette; Rodrigues, Angélica Nogueira; Moretti, Renato; Cândido, Eduardo Batista; Reis, Ricardo dos; Santiago, Aline Evangelista; Filho, Agnaldo Lopes da Silva (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The present study aims to obtain basic demographic information, the level of interest and of training in gynecology oncology among Brazilian obstetricians and gynecologists (OB-GYNs) to create a professional profile.Methods An online questionnaire was sent to 16,008 gynecologists affiliated to the Brazilian Federation of Associations of Gynecology and Obstetrics (FEBRASGO, in the Portuguese acronym). We considered gynecologists dedicated to gynecologic oncology (OB-GYNs ONCO) those who self-reported that > 50% of their daily practice consists in working with women's cancer care.Results A total of 1,608 (10%) of 16,008 FEBRASGO members responded. The OB-GYNs are concentrated in the southern and southeastern states of Brazil. Gynecologic oncology was considered the 8th greatest area of interest in gynecology among the OB-GYNs. A total of 95 (5.9%) of the OB-GYNs were considered OB-GYNs ONCO. Obstetricians and gynecologists are actively engaged in cancer care: > 60% of them dedicate up to 25% of their daily practice to oncology. The role of the physicians in screening and prevention, diagnosis, in the treatment of precancerous lesions, and in low complexity surgical procedures is notably high. Gynecologists dedicated to gynecologic oncology in Brazil have a heterogeneous, nonstandardized and short training period in gynecologic oncology. These professionals had a more significantly role in performing medium- and high-complexity operations compared with OB-GYNs (65.2% versus 34%, and 47.3% versus 8.4%, respectively).Conclusion The role of OB-GYNs and of OB-GYNs ONCO appears to be complementary. Obstetricians and gynecologists act more often in screening and prevention and in low-complexity surgical procedures, whereas OB-GYNs ONCO are more involved in highly complex cases. Strategies to raise standards in cancer training and to encourage the recognition of gynecologic oncology as a subspecialty should be adopted in Brazil.
Keywords: gynecology; women – diseases; oncology; cancer – surgery; gynecologists; obstetricians